Tumor Suppressor and Oncogenic miRNA Expressions in Patients with Type I Gaucher Disease and Carriers - Uzen, Ramazan; Bayram, Fahri; Dursun, Huseyin; Kardas, Fatih; Cakir, Mustafa; Sohel, Md Mahmodul Hasan; Cucer, Nurhan; Eken, Ahmet; Donmez-Altuntas, Hamiyet (MicroRNA, 2025)
Introduction Gaucher disease (GD) occurs due to a mutation in the glucosylceramidase (GBA) gene and is a common lysosomal storage disease. It is well known that there is a strong association between the abnormal expression of miRNAs and various diseases including cancer. These abnormally expressed miRNAs can be used as biomarkers. Interestingly, several studies have reported a linkage between GD with an increased risk of cancer. Therefore, in the current study, we investigated the expression levels of selected miRNAs that are associated with cancers that might have potential use as biomarkers in GD. Methods Blood samples were collected from 24 healthy volunteers, 6 carriers, and 20 treated patients with type 1 GD. A reverse transcription-quantitative real-time PCR (RT-qPCR) platform was used to analyze the miRNA expression levels. Results While carriers had lower relative expressions of miRNA-15a with tumor suppressor effect, and miRNA-150 and miRNA-181b with oncogene effect, treated patients with type 1 GD had lower relative expressions of miRNA-15a and miRNA-125b with tumor suppressor effect and higher relative expression miRNA-21 with oncogene effect (p<0.001, p<0.05, p<0.01, p<0.05, p<0.001, and p<0.05, respectively). Conclusion The results suggested that the downregulation of miRNA-15a and miRNA-125b expressions with tumor suppressor effect and the upregulation of miRNA-21 expression with oncogene effect can be indicated to an increased risk for cancers such as multiple myeloma (MM), B-cell lymphoma, leukemia, and hepatocellular carcinoma (HCC) in GD.
Keywords: miRNA150